UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN QUIZIZZ PADA MATERI BAKTERI KELAS X.E.7 MAN 2 KOTA PADANG - Hazirin, Tasya Humaira; Ardi, Ardi; Suryanef, Suryanef; Efida, Yanti (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Issues with learning activities can negatively impact student learning outcomes because students may not fully engage with or pay attention to the material presented. This study aims to assess the improvement in student activity through the implementation of the Problem Based Learning (PBL) model supported by Quizizz, as well as the impact on student learning outcomes. The research is a Classroom Action Research, with subjects being 35 students from class X.E.7 at MAN 2 Padang City for the 2024/2025 academic year. Data was collected using activity observation sheets and objective tests. The findings show that after applying the PBL model with Quizizz, student activity in learning about bacteria increased. In Cycle I, the activity level was at 27.85%, which improved to 63.1% in Cycle II. Student learning outcomes also improved, as evidenced by a rise in the percentage of students achieving classical learning completeness—from 48.57% in Cycle I, with an average score of 73.25, to 91% in Cycle II, with an average score of 95.71. Therefore, this research concludes that the PBL model supported by Quizizz effectively enhances both student activity and learning outcomes in the X.E.7 class on bacterial material at MAN 2 Padang City.